PAPAYA LEAF POWDER EXTRACT (Carica papaya L.) TO CONTROL THE WHITEFLY (Bemisia tabaci Genn.) ON RED CHILI PLANTS (Capsicum annum L.) - Syahira Khairina Panggabean (Agritech: Jurnal Fakultas Pertanian Universitas Muhammadiyah Purwokerto, 2022)
Bemisia tabaci Genn. is a pest of red chili plants. Bemisia tabaci Genn pest control is usually carried out using synthetic chemical insecticides, but inappropriate use will have a negative impact on the environment, so another alternative that is safer and more environmentally friendly is the use of insecticide papaya leaf powder extract. This study aimed to obtain a concentration of papaya leaf powder extract (Carica papaya L.) which is effective in controlling whitefly pests (Bemisia tabaci Genn.) on red chili (Capsicum annum L.). The research was at the Experimental Garden and Plant Pest Laboratory, Faculty of Agriculture, Riau University from Juni to August 2021. The experiment using a completely randomized design (CRD) with 6 treatments and 4 replications so that 24 experimental units were obtained. The concentration of papaya leaf powder extract used as treatment was 0 g.l-1 water, 20 g.l-1 water, 40 g.l-1 water, 60 g.l-1 water, 80 g.l-1 water, dan 100 g.l-1 water. The results showed that the concentration of papaya leaf powder extract 60 g.l-1 water was an effective concentration in controlling B. tabaci pests because it was able to mortality B. tabaci pests by 85% with an initial time of death of 5.25 hours after application and a lethal time of 50 at 18.75 hours after application.Keywords: Bemisia tabaci Genn., Carica papaya L, and Capsicum annum L